DEVELOPMENT OF INTERACTIVE CONTENT IN WEBSITE LEARNING MEDIA TO ADDRESS STUDENT MISCONCEPTIONS ABOUT THE GREENHOUSE EFFECT - Dewi, Syva Lestiyani; Kurniawan, Dede Trie; Sukardi, Rendi Restiana (Universitas Tanjungpura, 2024)
This study addresses the pressing need to improve students' comprehension of the greenhouse effect by leveraging innovative website-based Augmented Reality (AR) learning media. The purpose is to explore the effectiveness of this media in mitigating misconceptions surrounding the greenhouse effect while providing practical solutions for educators. The research methodology combines qualitative Design and Development (DD) approaches with quantitative measures to comprehensively evaluate the impact of AR learning media on students' understanding. Results demonstrate a significant increase of over 50% in student comprehension post-media use, validated by expert assessments and positive teacher feedback. Students reported overcoming prior misconceptions through the media's interactive approach. The study emphasizes the necessity of identifying key elements for effective AR learning, recommending comprehensive teacher training, content updates, and long-term impact assessments. The holistic approach employed unveils insights into how learning media can effectively reduce misconceptions, thereby enhancing awareness of crucial environmental issues like the greenhouse effect.